Spinal Tolerance and Dependence: Some Observations on the Role of Spinal N-Methyl-D-Aspartate Receptors and Phosphorylation in the Loss of Opioid Analgesic Responses - Tony L Yaksh; Xiao-Ying Hua (Pain Research and Management)
The continuous delivery of opiates can lead to a reduction in analgesic effects. In humans, as in other animals, some component of this change in sensitivity seems likely to have a strong pharmacodynamic component. Such loss of effect, deemed to be tolerance in the present article, can be readily demonstrated in animals with repeated bolus and continuous intrathecal infusion of mu and delta opioids and alpha-2 adrenergic agonists. Research has shown that this loss of effect can be diminished by concurrent treatment with N-methyl-D-aspartate (NMDA) receptor antagonists and by the suppression of the activity of spinal protein kinase C (PKC). This suggests in part the probable role of PKC-mediated phosphorylation in the right shift in the dose-effect curves observed with continuous opiate or adrenergic exposure. Importantly, this right shift is seen to occur in parallel with an increase in the phosphorylating activity in the dorsal horn and in the expression of several PKC isozymes. The target of this phosphorylation is not certain. Phosphorylation of the NMDA receptor enhances its functionality, while phosphorylation of the opioid receptor or associated channels seems to diminish their activity or to enhance internalization. While the focus is on several specific components, the accumulating data emphasize the biological complexity of these changes in spinal drug reactivity.